Effect of deprivation on in vitro fertilisation outcome: a cohort study. (6th December 2019) - Richardson, AL; Baskind, NE; Karuppusami, R; Balen, AH
Abstract : Objective: To determine whether socioeconomic deprivation affects IVF outcome independent of the number of cycles undertaken. Design: A retrospective review of prospectively collected data. Setting: A tertiary level fertility clinic in the North of England. Population: All participants undergoing their first fresh single‐embryo transfer, funded by the National Health Service (NHS), between January 2012 and December 2017. Methods: For each case, identified from the clinic database, we recorded the following: age; body mass index; FSH; number of eggs retrieved; ethnicity; cause of subfertility; stage of embryo transfer; and whether any adjuncts i.e. EmbryoGlue ® or Time Lapse Imaging were used. Socio‐economic deprivation was assessed using the Index of Multiple Deprivation (IMD) determined by the residential postcode. Main outcome measures: Clinical pregnancy (CP) and live birth (LB) rates across IMD quintiles. Results: Three thousand ninety‐one women were included. Overall, CP and LB rates were 35.9% and 31.3% respectively. CP rates increased significantly from 31.0% in the most deprived group to 38.8% in the least deprived group ( P  < 0.01). Similarly, LB rates were significantly lower in the most deprived group compared with the least deprived group (26.8 versus 35.4%, P  < 0.01). After adjusting for confounding variables, women in the least deprived group were significantly more likely to have a LB (aRR 1.18, 95% CI 1.00–1.39) than women in the most deprived group. Conclusions: More socio‐economically deprived patients are significantly less likely to achieve a LB than less deprived patients independent of the number of cycles of IVF undertaken. Tweetable abstract: More deprived patients are less likely to have a LB per cycle of IVF than less deprived patients. Tweetable abstract: More deprived patients are less likely to have a LB per cycle of IVF than less deprived patients.